The plastid genome and phylogenetic status of Sinosenecio eriopodus C. Jeffrey & Y. L. Chen 1984 (Asteraceae) - Yao Sun; Cheng Zhang; Jingyi Peng; Qiang Zhou (Mitochondrial DNA. Part B. Resources)
The genus Sinosenecio B. Nordenstam (1978) is a challenging taxonomic group with complex infrageneric relationships. Here, we newly report the plastid genome of S. eriopodus (Cumm.) C. Jeffrey & Y. L. Chen (1984). Whole genome exhibited a typical quadratic structure with a total size of 151,212 bp and 132 genes. We revealed for the first time that the matK and rpoA were positively selected genes within Sinosenecio. Phylogenetic reconstruction based on whole plastid genome sequences indicated that S. eriopodus was not clustered into a monophyletic clade with members belonging to the S. oldhamianus group of Sinosenecio but rather was closely related to some genera in the subtribe Tussilaginae s.s. of Asteraceae.